Bio-oil synthesis from cassava pulp via hydrothermal liquefaction: Effects of catalysts and operating conditions - Thanakrit Nonchana; Kulachate Pianthong (International Journal of Renewable Energy Development, 2020)
The influence of catalysts and operating conditions on the conversion and yield of bio-crude oil from CP via the hydrothermal liquefaction technique (HTL) were studied. HTL is commonly used to convert CP to bio-crude oil (BCO). Three independent factors—reaction temperatures (250–350 °C), reaction times (30–90 min), and CP concentrations (5–20 wt.%)—were investigated. Proximate analysis showed that CP comprises 84.61% volatile matter and 13.59% fixed carbon. The ultimate analysis demonstrated that CP has carbon and oxygen levels of 44.86% and 46.91%, respectively. Thermogravimetric analysis showed that CP begins to decompose at temperatures between 250–350 °C. The results show that KOH is the most suitable catalyst because it provides the highest BCO yield when compared to other catalysts under the same operating conditions. We found that the ideal operating conditions for maximizing BCO performance are 250 °C, pressure of 17.0 MPa, 90 min, 5 wt.%. Under these conditions, Fourier transforms infrared analysis showed that the most abundant chemical bonds found in BCO were CH3-O, CH3-C, and CH3. The findings of the CHNS analysis showed that BCO has an H/C ratio of 2.25, similar to that of petroleum and bio-diesel. Results from a gas chromatograph-mass spectrometer indicate that a fatty acid group is the main component of BCO.